Synthesis and Self-Assemble Nanofibers of Tetra Phenoxy Substituted Nickel Phthalocyanine - Gao, Junshan; Huang, Guoqing; Du, Xiguang (Asian Journal of Chemistry, 2014)
Tetra phenoxy substituted nickel phthalocyanine nanofibers were synthesized in large scale by self-assemble. The FESEM and HRTEM micrographs indicated that the sizes of the fibers are 20-60 nm in width and 0.2-5 μm in length. The formation mechanism of nickel phthalocyanine fibers was discussed and studied by XRD and UV-visible spectra. The nickel phthalocyanine nanofibers have potential application on organic function devices.